2018
DOI: 10.7759/cureus.3390
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed Diabetes in Patients Admitted to a Clinical Decision Unit from the Emergency Department: A Retrospective Review

Abstract: ObjectivesDiabetes is a debilitating disease that affects the way the body uses or produces insulin. Research evaluating the usefulness in screening patients admitted to a clinical decision unit (CDU) from the emergency department (ED) has been limited.MethodsA retrospective chart review of patients admitted to a CDU from the ED was performed. Patients included were > 18-year-old who were observed in the CDU, had blood glucose drawn greater than eight hours after admission, and who had not been previously diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
(12 reference statements)
0
7
0
2
Order By: Relevance
“…Many studies have shown that RPG can detect significant proportion of undiagnosed DM and prediabetes when combined with appropriate definitive diagnostic test like OGTT, FPG and A1C 9 . A study conducted by Friedman et al 10 , in 2013 revealed a frequency of 12.5% of DM when elevated screening RPG was followed with OGTT while another study conducted by Barasch et al 11 , revealed frequency of 12.2% and 5.7% for DM and prediabetes respectively when healthy individuals underwent screening RPG.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that RPG can detect significant proportion of undiagnosed DM and prediabetes when combined with appropriate definitive diagnostic test like OGTT, FPG and A1C 9 . A study conducted by Friedman et al 10 , in 2013 revealed a frequency of 12.5% of DM when elevated screening RPG was followed with OGTT while another study conducted by Barasch et al 11 , revealed frequency of 12.2% and 5.7% for DM and prediabetes respectively when healthy individuals underwent screening RPG.…”
Section: Introductionmentioning
confidence: 99%
“…Of the population, 70.7% of individuals declared themselves to be of White ethnicity, 3.1% of Asian background and 1.1% of Black background, with 23.1% unstated. The median number of admissions was 2, 1,3 and median length of admission was 1.3 (0.3, 3.5) days.…”
Section: Resultsmentioning
confidence: 99%
“…The authors report that automatically triggering HbA1c measurements in their intervention group did not lead to increased rates of diabetes diagnoses in hospital 6 . Another Australian study used a cut‐off of 5.5 mmol/L among people presenting to the emergency department to trigger HbA1c measurement 3 . They found that 11% of those tested had HbA1c measurements consistent with diabetes 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Akan tetapi penderita DM yang tidak terdiagnosis sebanyak 7,6 juta orang atau setara dengan 73,7%. Penderita DM sering tidak terdiagnosis selama bertahun-tahun, sehingga mereka baru sadar akan penyakitnya setelah muncul komplikasi (Sop et al, 2018). Kondisi ketidaktahuan mengalami DM ini tidak hanya terjadi di negara yang sedang berkembang, studi penelitian yang dilakukan oleh Bernal-Soriano et al (2021) menemukan bahwa 77% kebutuhan perawatan diabetes tidak terpenuhi akan menimbulkan beberapa komplikasi makro dan mikro Diabetes Melitus.…”
Section: Pendahuluanunclassified